2019
DOI: 10.1177/1474515119845972
|View full text |Cite
|
Sign up to set email alerts
|

Ability of non-physicians to perform and interpret lung ultrasound: A systematic review

Abstract: Background: Lung ultrasound is a useful tool in the assessment of pulmonary congestion in heart failure that is typically performed and interpreted by physicians at the point-of-care. Aims: To investigate the ability of nurses, students, and paramedics to accurately identify B-lines and pleural effusions for the detection of pulmonary congestion in heart failure and to examine the training necessary. Methods and results: We conducted a systematic review and searched online databases for studies that investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 50 publications
3
22
0
2
Order By: Relevance
“…Hospital readmission of patients with HF is a major public health problem, and residual pulmonary congestion at discharge is one of the leading responsible conditions. In last years, LUS has emerged as an attractive tool in HF because of it is a rapid point‐of‐care test with a fast learning curve and a high inter‐observer agreement 1,26,27 . Moreover, our group recently showed that a LUS‐guided strategy significantly improved the combined endpoint of urgent visit, hospitalization for worsening HF, and death during a 6 month follow‐up in patients after HF admission 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital readmission of patients with HF is a major public health problem, and residual pulmonary congestion at discharge is one of the leading responsible conditions. In last years, LUS has emerged as an attractive tool in HF because of it is a rapid point‐of‐care test with a fast learning curve and a high inter‐observer agreement 1,26,27 . Moreover, our group recently showed that a LUS‐guided strategy significantly improved the combined endpoint of urgent visit, hospitalization for worsening HF, and death during a 6 month follow‐up in patients after HF admission 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In last years, LUS has emerged as an attractive tool in HF because of it is a rapid point-of-care test with a fast learning curve and a high inter-observer agreement. 1,26,27 Moreover, our group recently showed that a LUS-guided strategy signifi- cantly improved the combined endpoint of urgent visit, hospitalization for worsening HF, and death during a 6 month follow-up in patients after HF admission. 11 Then, it is conceivable that adding LUS to clinical practice will reinforce the ability of clinicians to promptly detect and treat fluid overload and, ultimately, improve the prognosis of patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Although novice POCUS operators can attain basic competency in image acquisition and image interpretation with relatively brief training, 11,33 expert use of any test requires a more complex skill set to integrate test results into clinical decision-making. This higher order skill includes the ability to combine an accurate pretest probability with knowledge of the test characteristics and limitations of the POCUS examination performed to arrive at an accurate posttest probability and appropriate management plan.…”
Section: Trainingmentioning
confidence: 99%
“…Two recent randomized controlled trials demonstrated the use of point-of-care lung ultrasound both decreased length of stay and number of urgent visits in patients recently hospitalized for heart failure [ 11 , 12 ]. Further, lung ultrasound is a relatively easy POCUS application for to learn [ 13 ] and perform [ 14 ]. Although POCUS has become more readily available in all hospitals over the past 25 years, only 4% of respondents indicated POCUS was among their most useful bedside tools, suggesting a provider training gap exists and should be a focus of future quality improvement efforts.…”
Section: Discussionmentioning
confidence: 99%